TWEAK/Fn14 distinctly remodels the transcriptomic and epigenetic landscape in triple negative breast cancer to drive its progression - Sim, Nicholas Yang-U (Nanyang Technological University, 2023)
Breast cancer is the most prevalent malignancy in women and one of the leading causes of cancer-related deaths globally. Of which, roughly 20% of cases are Triple Negative Breast Cancers (TNBC) which are highly aggressive and lack hormone receptors, rendering standard systemic therapy ineffective. Consequently, TNBCs account for a disproportionate number of breast cancer deaths compared to other breast cancer subtypes, highlighting an urgent need for novel TNBC targeted therapies. Recently, the Fibroblast Growth Factor-Inducible 14 (Fn14) receptor was found to be overexpressed in Estrogen Receptor (ER) negative breast cancers and associated with worse prognosis, making it an attractive target for therapy. However, our understanding of the Fn14 signalling mechanism and its role in breast cancer is very limited.